Analytical Procedure Development paragraph Extraction and Pre - Iron Concentration in Production Water Samples Using Cloud Point Extraction and Atomic Absorption Spectrometry Flame - Tamyris de Aquino Gondim (2015)
Produced water from petroleum industry is characterized by their high salinity and its complex composition. Depending on its origin, the produced water may contain a variety of chemicals such as organic salts, aliphatic hydrocarbons, polycyclic aromatic hydrocarbons (HPA), potentially toxic metals and radioactive materials. Therefore, the disposal of these production waters can be considered a major problem for the oil industry, since the produced water must be characterized and treated before being discarded at sea. This characterization includes evaluating the concentration of inorganic elements; however, the determination of these elements is not a simple procedure because of the complexity of the sample matrix, which has high salinity causing scattering and suppression of analytical signal in spectrometric analysis. This work proposes a methodology to iron quantification in saline produced water from oil industry by flame atomic absorption spectrometry (FAAS) after cloud point extraction (EPN). The procedure is based on the cloud point extraction using PAN as complexing agent and Triton X-114 as surfactant. The parameters that can influence the CPE were studied and optimized using a Box-Behnken design in order to get the best conditions for iron extraction. The CPE has the advantage of being a simple, low cost, in accordance with the green chemistry, selective and preconcentration factor compatible with other traditional methods. The proposed method was validated by obtaining a limit of quantification of 0.010 mg L-1 and detection limit of 0.003 mg L-1. Linear response within 0,02 and 0,40 mg L-1 . The precision of the method was evaluated in terms of repeatability, obtaining a coefficient of variation of CVm 0.67 %. The accuracy of the method was assessed by recovery experiments of Fe fortification in three concentration levels that presented recovery of Rm 101.58 %. The method applied with satisfactory performance to determine iron production waters.